A Roadmap to Robot Motion Planning Software Development (2009)
PhD programs and graduate studies in robotics usually include motion planning among its main subjects. Students that focus their research in this subject find themselves trapped in the necessity of programming an environment where to test and validate their theoretic contributions. The programming of this robot motion planning environment is a big challenge. It requires on the one hand good programming skills involving the use of software development tools, programming paradigms, or the knowledge of computational complexity and efficiency issues. On the other hand it requires coping with different related issues like the modeling of objects, computational geometry problems and graphical representations and interfaces. The mastering of all these techniques is good for the curricula of roboticists with a motion planning profile. Nevertheless, the time and effort devoted to this end must remain reasonable. Within this framework, the aim of this paper is to provide the students with a roadmap to help them in the development of the software tools needed to test and validate their robot motion planners. The proposals are made within the scope of multi-platform open source code.